POLA REKRUTMEN CALON LEGISLATIF PEREMPUAN PARTAI POLITIK PERINDO PADA PEMILIHAN UMUM 2019 DI SUMATERA UTARA - Madin Silalahi; Parlindungan Marpaung; Dolly Tua Mulia Raja Panjaitan; Bastian Da’o (JURNAL GOVERNANCE OPINION, 2019)
Political parties are political organizations that have the authority to recruit legislative candidate figures in each general election. The low participation of women in politics is caused by women assuming that politics is men's business and advancing as a legislative candidate only spends money. This study aims at finding out how the Perindo Party's DPW process in recruiting women who have the ability to be promoted as legislative candidates. The study uses a qualitative descriptive approach. DPW Perindo Party of North Sumatra carries out the function of political recruitment in recruiting women legislative candidates for the North Sumatra DPRD. The results showed that the North Sumatra Perindo DPW carried the North Sumatra Province DPRD candidates, there were 59 men with a percentage of 64.8% while women legislative candidates numbered 32 people with a percentage of 35.2%. Based on the results of research conducted, the recruitment process is carried out openly by reporting acceptance of registration through banners, billboards and the official website of the Perindo Party. It is followed by the implementation of fit and proper test, compilation of a provisional list of candidates. After that the registration was done in the General Election Commission (KPU) and the official announcement of permanent candidates for legislative candidates through the mass media. Recruitment is carried out without any element of female discrimination. The obstacle in recruiting is the difficulty in finding female figures who are willing to run for legislative candidates.